MAXIMAL DEPTHS OF BOOLEAN FUNCTIONS (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2004)
Given any Boolean function, there is an upper bound of its depths with respect to arbitrary complete sets of such functions. We prove the algorithmic computability of the largest of these depths.